MOST COMMON DISEASE - STILL NO CURE? THE IMPACT OF DIETARY SUPPLEMENTS ON THE COMMON COLD - A SYSTEMATIC REVIEW - Zuzanna Rafałowska,; Stanisław Rutz,; Anna Wojtala,; Julia Kret,; Aleksandra Wyrostkiewicz,; Jagoda Pałubska,; Oliwer Muller,; Aleksander Sadkowski,; Paulina Bigda,; Jan Gdula,; Lilianna Zielińska,; Michał Szpunar,; et al. (International Journal of Innovative Technologies in Social Science, 2026)
Introduction. The common cold is one of the most prevalent acute respiratory infections worldwide and represents a significant public health and socioeconomic burden. Due to the lack of curative antiviral therapies and the limited effectiveness of conventional symptomatic treatment, there is growing interest in dietary supplements and herbal preparations that may prevent infection, shorten disease duration, or alleviate symptom severity.Materials and Methods. A structured literature search was conducted using PubMed and Google Scholar databases. Priority was given to systematic reviews, meta-analyses, and randomized controlled trials evaluating the effects of Vitamin D, Vitamin C, cloves (Syzygium aromaticum), zinc, Black elderberry (Sambucus nigra), ginseng (Panax spp.), echinacea (Echinacea spp.), Pelargonium sidoides, and Black seed (Nigella sativa) on the prevention and treatment of the common cold. Studies were assessed according to evidence-based medicine principles, with emphasis on clinical outcomes such as incidence, duration, and severity of symptoms.Results: The reviewed evidence indicates that zinc lozenges and standardized echinacea preparations provide the most consistent benefits in reducing the duration and severity of common cold symptoms when administered early. Among the analyzed interventions, echinacea was the only one that demonstrated a reproducible preventive effect against the development of the common cold. Black elderberry and Pelargonium sidoides were associated with clinically meaningful reductions in symptom severity and illness duration, although evidence for their preventive efficacy remains limited. Vitamin C and Vitamin D showed modest benefits primarily in specific populations, such as individuals exposed to intense physical stress or those with Vitamin D deficiency. Evidence regarding ginseng was inconsistent, while cloves and Nigella sativa lacked robust clinical trials specifically addressing the common cold despite encouraging preliminary findings.Conclusions. Several dietary supplements and herbal preparations may offer therapeutic benefits in the management of the common cold; however, their effectiveness varies considerably depending on formulation, dosage, timing of administration, and population studied. Echinacea emerges as the most promising agent for prevention, while zinc, elderberry, and Pelargonium sidoides appear most relevant for symptom reduction and illness shortening. Further high-quality, standardized randomized controlled trials are required to clarify preventive efficacy and establish clear clinical recommendations.